The Effect of Hedonic Shopping Value and Atmosphere Store on Impulse Buying with Positive Emotion as Intervening Variables on Ketos Consumers (Kediri Town Square) - Nurul Hidayah; Novi Marlena (Institute of Computer Science (IOCS), 2021)
This study aims to explain and analyze the effect of hedonic shopping value and store atmosphere on impulse buying with positive emotion as an intervening variable on Kediri Townsquare consumers. The population in this study are consumers who have shopped and visited Kediri Townsquare. This research is a quantitative descriptive type for the sampling technique using judgmental sampling which is part of purposive sampling with 100 respondents. The data source uses primary data in the form of an online questionnaire via a google form link. The analytical technique used is path analysis, F test and coefficient of determination, and hypothesis testing (T test) using the SPSS version 24 application. The results of this study indicate that hedonic shopping value has a positive and significant effect on positive emotion , the store atmosphere variable has a positive effect on positive emotion, the positive emotion variable has no significant effect on impulse buying, then the hedonic shopping value variable has a positive and significant effect on impulse buying and the store atmosphere variable has no negative effect on impulse buying.